Effect of different drilling techniques on high-cycle fatigue behavior of nickel-based single-crystal superalloy with film cooling hole - Zhang Zhijin (De Gruyter, 2021)
The flat plate specimens of nickel-based single-crystal superalloy with 14 film cooling holes, which made by different drilling techniques, were used to study the high-cycle fatigue (HCF) properties at 980°C in an ambient atmosphere. At the same time, the electrical discharge machining (EDM) specimens with a single hole were also used to study the HCF properties under different temperatures. The hole and fracture micrographs were analyzed by scanning electron microscope. The results indicated that different drilling techniques have a great influence on HCF life. The fatigue limit of the millisecond laser drilling is 353 MPa, while the EDM is 359 MPa and the electro-stream machining (ESM) is 378 MPa. The fatigue life decreases gradually with the temperature increasing. The fatigue limit of EDM specimens with a single hole at 900°C, 980°C, and 1,050°C are 472, 430, and 293 MPa, respectively. The destruction of the specimens is a typical multisource rupture, and the fracture morphology includes three parts: the cracks sources around the film cooling hole, the propagation zone along the {001} planes, and instant rupture zone along the {111} planes.